Analisis Karakter Kerja Keras Siswa Kelas VII C dan VII E SMPN 1 Kota Jambi : Analysis of Student's Hard Work Character at SMPN 1 Jambi City - Rusnaningsih, Rusnaningsih; Ningtyas, Sri Sukma Ajeng (Universitas Muhammadiyah Sidoarjo, 2018)
This study purposes to analyze the character of the hard work of students of class VII C and class VII E SMP Negeri 1 Jambi City. This study uses descriptive quantitative research methods. While the type of research used is observation with a test assessment instrument in the form of a questionnaire with hard working character variables. The subjects of this study were students of class VII C and VII E SMP Negeri 1 Kota Jambi, with a total number of respondents as many as 61 respondents. The data analysis technique used is descriptive statistical analysis techniques. The results of the study stated that the character questionnaire of hard work of students in class VII C on average belonged to the category